Acoustic characteristics of synthesized signals of Chinese bahaba (Bahaba taipingensis) - Wei, Chong; Huang, Jiali; Dai, Ming; Zhang, Siyu; Huang, Honghui; Zhang, Yu (2021)
As a member of Sciaenidae, Chinese bahaba (Bahaba taipingensis) generate sounds using sonic muscles to drive the swim bladder. In this study, the drumming sounds of Chinese bahaba in two groups differing in body size were recorded in an indoor aquarium and an outdoor pond. A piecewise exponential oscillation function was developed to synthesize the signals with a good agreement. Statistical comparisons found that the oscillation frequency and damping coefficient (part 1) of synthesized signals from larger-sized fish were lower. The results suggest that the acoustic characteristics of Chinese bahaba signals are related to fish morphology as the physiological age alters.